Directional characteristic of a circular plate vibrating under the external pressure - W. RDZANEK (Archives of Acoustics)
In this paper, the problem of acoustic wave radiated and received by a lip restrained circular plate vibrating in a rigid baffle is distributed. The vibratory system is found in the lossless and homogeneous liquid medium. The dynamics influence of the wave emitted by plate on its vibration form has been omitted as well as the losses in plate have been neglected. The axially symmetric vibration induced by the sinusoidal varried in time external pressure has been considered. By assuming the known distribution of pressure forcing vibration, a simple expression has been found allows to determine the directional characteristic.